Endocannabinoid signaling regulates post-operative delirium through glutamatergic mediodorsal thalamus-prelimbic prefrontal cortical projection - Liu, Yang; Jia, Sansan; Wang, Jiajia; Wang, Dan; Zhang, Xinxin; Liu, Huiqing; Zhou, Fang; Zhang, Zhihao; Li, Qi; Dong, Hailong; Zhong, Haixing (Frontiers in Aging Neuroscience, 2022)
Background Post-operative delirium (POD), a common post-operative complication that affects up to 73. 5% of surgical patients, could prolong hospital stays, triple mortality rates, cause long-term cognitive decline and dementia, and boost medical expenses. However, the underlying mechanisms, especially the circuit mechanisms of POD remain largely unclear. Previous studies demonstrated that cannabis use might cause delirium-like behavior through the endocannabinoid system (eCBs), a widely distributed retrograde presynaptic neuromodulator system. We also found that the prelimbic (PrL) and intralimbic (IL) prefrontal cortex, a crucial hub for cognition and emotion, was involved in the eCBs-associated general anesthesia recovery. Objectives The present study aimed to investigate the role of eCBs in POD development, and further clarify its neuronal specificity and circuit specificity attributed to POD. Methods According to a previous study, 2 h of 1.4% isoflurane anesthesia and simple laparotomy were conducted to establish the POD model in C57/BL6 mice aged 8–12 weeks. A battery of behavioral tests, including the buried food, open field, and Y maze tests, were performed at 24 h before anesthesia and surgery (AS) and 6 and 9 h after AS. The behavioral results were calculated as a composite Z score for the POD assessment. To explore the dynamics of eCBs and their effect on POD regulation, an endocannabinoid (eCB) sensor was microinjected into the PrL, and the antagonists (AM281 and hemopressin) and agonist (nabilone) of type 1 cannabinoid receptor (CB1R), were administered systemically or locally (into PrL). Chemogenetics, combined Cre-loxP and Flp-FRT system, were employed in mutant mice for neuronal specificity and circuit specificity observation. Results After AS, the composite Z score significantly increased at 6 and 9 but not at 24 h, whereas blockade of CB1R systemically and intra-PrL could specifically decrease the composite Z score at 6 and 9 h after AS. Results of fiber photometry further confirmed that the activity of eCB in the PrL was enhanced by AS, especially in the Y maze test at 6 h post-operatively. Moreover, the activation of glutamatergic neurons in the PrL could reduce the composite Z score, which could be significantly reversed by exogenous cannabinoid (nabilone) at 6 and 9 h post-operatively. However, activation of GABAergic neurons only decreased composite Z score at 9 h post-operatively, with no response to nabilone application. Further study revealed the glutamatergic projection from mediodorsal thalamus (MD) to PrL glutamatergic neurons, but not hippocampus (HIP)-PrL circuit, was in charge of the effect of eCBs on POD. Conclusion Our study firstly demonstrated the involvement of eCBs in the POD pathogenesis and further revealed that the eCBs may regulate POD through the specific MDglu-PrLglu circuit. These findings not only partly revealed the molecular and circuit mechanisms of POD, but also provided an applicable candidate for the clinical prevention and treatment of POD.